Validation of Standard and New Criteria for the Differential Diagnosis of Narrow QRS Tachycardia in Children and Adolescents. Issue 51 (December 2015) - Deutsch, Karol; Stec, Sebastian; Kukla, Piotr; Morka, Aleksandra; Jastrzebski, Marek; Baszko, Artur; Pitak, Maciej; Sledz, Janusz; Fijorek, Kamil; Mazij, Mariusz; Ludwik, Bartosz; Gubaro, Marcin; et al.
Abstract : Abstract: To establish an appropriate treatment strategy and determine if ablation is indicated for patients with narrow QRS complex supraventricular tachycardia (SVT), analysis of a standard 12-lead electrocardiogram (ECG) is required, which can differentiate between the 2 most common mechanisms underlying SVT: atrioventricular nodal reentry tachycardia (AVNRT) and orthodromic atrioventricular reentry tachycardia (OAVRT). Recently, new, highly accurate electrocardiographic criteria for the differential diagnosis of SVT in adults were proposed; however, those criteria have not yet been validated in a pediatric population. All ECGs were recorded during invasive electrophysiology study of pediatric patients (n = 212; age: 13.2 ± 3.5, range: 1–18; girls: 48%). We assessed the diagnostic value of the 2 new and 7 standard criteria for differentiating AVNRT from OAVRT in a pediatric population. Two of the standard criteria were found significantly more often in ECGs from the OAVRT group than from the AVNRT group (retrograde P waves [63% vs 11%, P  < 0.001] and ST-segment depression in the II, III, aVF, V1–V6 leads [42% vs 27%; P  < 0.05]), whereas 1 standard criterion was found significantly more often in ECGs from the AVNRT group than from the OAVRT group (pseudo r′ wave in V1 lead [39% vs 10%, P  < 0.001]). The remaining 6 criteria did not reach statistical significance for differentiating SVT, and the accuracy of prediction did not exceed 70%. Based on these results, a multivariable decision rule to evaluate differential diagnosis of SVT was performed. These results indicate that both the standard and new electrocardiographic criteria for discriminating between AVNRT and OAVRT have lower diagnostic values in children and adolescents than in adults. A decision model based on 5 simple clinical and ECG parameters may predict a final diagnosis with better accuracy.